2013
DOI: 10.1155/2013/174659
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases and Review of the Literature: Primary Percutaneous Angiography and Antiplatelet Management in Patients with Immune Thrombocytopenic Purpura

Abstract: We report two cases of immune thrombocytopenic purpura (ITP) associated with acute coronary artery syndrome highlighting the interventions done in every case along with the medications used during intervention and as outpatient. The first case is that of a woman with ITP exacerbation while on dual antiplatelet therapy and the second case is that of a male presenting with non-ST elevation myocardial infarction (NSTEMI) while in a thrombocytopenic crisis. In both cases antiplatelet therapy was held and thrombopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
(35 reference statements)
1
19
0
Order By: Relevance
“…The precise mechanism of arterial thrombosis in ITP is unknown, but several explanations have been offered: Presence of large, immature, prothrombotic platelets, elevated platelet microparticles which promote coagulation, presence of antiphospholipid antibodies and anti-IIb/IIIa antibodies which target both platelets and endothelial cells due to antigenic mimicry [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanism of arterial thrombosis in ITP is unknown, but several explanations have been offered: Presence of large, immature, prothrombotic platelets, elevated platelet microparticles which promote coagulation, presence of antiphospholipid antibodies and anti-IIb/IIIa antibodies which target both platelets and endothelial cells due to antigenic mimicry [6].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that antiplatelet therapy is safe and well tolerated chronically when platelet count is >30 × 10 9 /L and should be discontinued only during the bleeding episode [6]. Withdrawal of clopidogrel and maintenance of antiplatelet therapy with aspirin alone has been described, too [1].…”
Section: Discussionmentioning
confidence: 99%
“…PCI, which was generally undertaken by BMS deployment, was performed with different platelet counts, ranging from 5,000/μL (10) to 78,000/μL (5). A DES was implanted in only one patient (13). Balloon angioplasty alone was successfully performed in two cases (2,6).…”
Section: Discussionmentioning
confidence: 99%
“…In the stent era, which is increasingly becoming the drug eluting stent (DES) era, patients require prolonged dual anti-platelet therapy (DAPT) to prevent stent thrombosis (ST). It has been reported that the temporary discontinuation of antiplatelet therapy could not be avoided due to the exacerbation of ITP during the clinical course after PCI with a bare metal stent (BMS) and a DES (5,13). Therefore, we have to carefully consider the treatment of patients with AMI with concomitant ITP.…”
Section: Introductionmentioning
confidence: 99%
“…5 Being a rare occurrence, clinical studies on ACS in ITP patients are scarce. Torbey et al (2013) reported two patients, aged 55 and 61 years, with ACS and ITP. 6 A review published in 2011, comparing the results of coronary artery bypass grafting (CABG) versus primary coronary intervention (PCI) in subjects with ITP found 32 patients with ITP who underwent CABG, mean age 63 ± 10 years, and 15 cases of ITP with PCI, mean age 62 ± 16 years.…”
Section: Introductionmentioning
confidence: 99%